2015
DOI: 10.1016/j.jaip.2014.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Household Costs Associated with Objectively Diagnosed Allergy to Staple Foods in Children and Adolescents

Abstract: Households with a child and/or adolescent with objectively diagnosed allergy to staple foods have higher total household costs than controls. Direct and indirect costs were significantly higher for cases versus controls amongst children only. Amongst both age groups, such allergy adversely impacted intangible costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
75
3
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(98 citation statements)
references
References 27 publications
(37 reference statements)
3
75
3
14
Order By: Relevance
“…In addition, a Swedish questionnaire study that included 144 children and adolescents with food allergies and 150 nonallergic controls reported higher total household costs for those with allergies (22). The annual total household costs were €3961 higher for children and €4792 higher for adolescents than for the controls (22). In addition, the higher annual healthcare costs were associated with food allergies in a European patient-based, cost-of-illness study (23).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, a Swedish questionnaire study that included 144 children and adolescents with food allergies and 150 nonallergic controls reported higher total household costs for those with allergies (22). The annual total household costs were €3961 higher for children and €4792 higher for adolescents than for the controls (22). In addition, the higher annual healthcare costs were associated with food allergies in a European patient-based, cost-of-illness study (23).…”
Section: Discussionmentioning
confidence: 98%
“…purchasing special food, direct and indirect medical costs and time off work) translating to $21.8 billion/year for the United States alone . A questionnaire‐based European study estimated that total household costs were higher by €3961 for children with confirmed food allergy and €4792 for adolescents compared with controls, with higher costs associated with a diagnosis of anaphylaxis . The EuroPrevall study examined the additional cost of care in those diagnosed with self‐reported food allergy in nine European countries, estimating an additional cost of International $927 per adult per year, with higher costs in those with more severe disease …”
Section: Counting the Economic Costmentioning
confidence: 99%
“…Yet, health-related quality of life does not appear to differ between the phenotypes [18]. Moreover, both phenotypes burden healthcare systems [19, 20], society [21] and households [21, 22]. …”
Section: Introductionmentioning
confidence: 99%